2015
DOI: 10.1111/sms.12555
|View full text |Cite
|
Sign up to set email alerts
|

Running performance and thermal sensation in the heat are improved with menthol mouth rinse but not ice slurry ingestion

Abstract: The purpose of this study was to compare the effects of a cooling strategy designed to predominately lower thermal state with a strategy designed to lower thermal sensation on endurance running performance and physiology in the heat. Eleven moderately trained male runners completed familiarization and three randomized, crossover 5-km running time trials on a non-motorized treadmill in hot conditions (33 °C). The trials included ice slurry ingestion before exercise (ICE), menthol mouth rinse during exercise (ME… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
132
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(154 citation statements)
references
References 39 publications
10
132
8
Order By: Relevance
“…Lowering the core temperature by ice ingestion allows for greater heat storage capacity during exercise, in turn delaying the onset of hyperthermia-induced fatigue [7]. Recently, however, some studies have found no beneficial effect of ice ingestion [12, 13]. These studies reported that participants began the endurance exercise within 5 min of consuming the final beverage, as such these strategies may not have been effective because of the short rest interval used.…”
Section: Introductionmentioning
confidence: 99%
“…Lowering the core temperature by ice ingestion allows for greater heat storage capacity during exercise, in turn delaying the onset of hyperthermia-induced fatigue [7]. Recently, however, some studies have found no beneficial effect of ice ingestion [12, 13]. These studies reported that participants began the endurance exercise within 5 min of consuming the final beverage, as such these strategies may not have been effective because of the short rest interval used.…”
Section: Introductionmentioning
confidence: 99%
“…Habitual menthol use may alter the threshold at which TRPM8 channels and the trigeminal nerve are stimulated [37][38][39][40], ultimately habituating thermal sensation [37,38]. Despite no statistically significant differences in the present investigation, menthol concentrations of 0.095-0.105% may lead to small increases in trigeminal stimulation, concomitantly conferring benefits such as an increase in ventilation [3,16], reduced thermal sensation [18] and thirst [14], and improved thermal comfort [9] when exposed to the oral cavity.…”
Section: Discussionmentioning
confidence: 62%
“…Menthol mouth swilling is considered a practical ergogenic strategy before and during exercise in hot environments [11,30] and has been used to improve performance during time trials [17,18] and time to exhaustion [16,31]. Perception of menthol mouth swill concentration may be highly individual in nature, with 200 gene variants of the receptor responsible for menthol detection (TRPM8 [32]).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations